Estudo detalhado dos solos do Campus do Cauamé da UFRR, Boa Vista, Roraima - Benedetti, Udine Garcia (2007)
This work has as objective to classify and to map in details the soil of Cauamé Campus of Federal University of Roraima aiming recommendations for supportable and manageable use so the results of this research will serve as support for studies developed at the Campus and in other areas of the savannah. The images and maps were processed by the Arc View GIS 8.1, ArcMap 8.1 and TrackMaker 3.8 programs, where maps of the soil were obtain inn scale 1:5.500 according to Embrapa. The soils were characterized as regards physical, morphorgical, chemical and mineral properties. For soil collection and area mapping were open 14 trenches and made 198 samples from September, 2006 to July, 2007.